PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN AKTIVITAS CSR DALAM DIMENSI TATA KELOLA, LINGKUNGAN, DAN SOSIAL TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2017-2018) - Darmawan Citrajaya; Imam Ghozali (Diponegoro Journal of Accounting, 2020)
This study aims to investigate the relationship between corporate social responsibility, governance dimension of CSR, environmental dimension of CSR, and social dimension of CSR on earnings management. The independent variable in this research is CSR, governance dimension of CSR, environmental dimension of CSR, and social dimension of CSR. While the dependent variable used in this study is earnings management.This study uses secondary data from the financial information provided on Bloomberg database of companies listed on the Indonesian Stock Exchange. Using purposive sampling method, the 92 samples selected from non-financial sector which published its financial statements from 2017-2018. Multiple regression analysis is the test used to study the relationship between CSR, governance dimension of CSR, environmental dimension of CSR, and social dimension of CSR on earnings management.The results show that environmental dimension of CSR may be an organizational device that has negative impact to earnings management practices. Furthermore, we found no significant impact of total CSR, governance, and social dimension of CSR on earnings management practices.